A study of fiber configuration in sliver fiber arrangement and its influence on sliver limit irregularity. Issue 23 (December 2019) - Yang, Jianping; Shen, Yuanying; Zhang, Hongqiang
Random fiber arrangement in slivers is the direct and intuitive factor resulting in sliver limit irregularity. In this study, by simulating the fiber arrangement in slivers, the effect of fiber configuration on sliver limit irregularity is investigated. The tracer fiber technique was employed to ascertain fiber straightness and the incidence of different fiber configurations in carded slivers. It is observed from the results that the majority of fibers are hooked in the carded sliver. It is fiber straightness rather than hook type that affects the sliver limit irregularity more; with the increase of fiber straightness, the sliver limit irregularity decreased. In addition, the simulation proposed in this study can not only portray fiber arrangement in slivers more practically, but also present sliver limit irregularity more accurately compared with the method mentioned in previous studies.